Strategies and Public Policies for Economic Recovery Post-Pandemic: The Role of Taxation According to Qualitative Studies - Tauhid Syukur, Alam (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This qualitative synthesis investigates the role of taxation in post-pandemic economic recovery, aiming to provide insights into effective policy strategies. Drawing upon a systematic review of qualitative literature from diverse disciplines such as economics, public policy, and taxation theory, the study explores the multifaceted nature of taxation's impact on recovery trajectories. Methodologically, the research employs thematic analysis to identify key themes and patterns emerging from the literature. The findings highlight taxation's critical role as a revenue-generating mechanism for governments facing fiscal deficits post-pandemic. Moreover, the study elucidates taxation's redistributive function in mitigating income inequality and promoting social cohesion through progressive tax policies. Tax incentives emerge as crucial tools for stimulating investment and innovation, fostering economic dynamism amidst recovery efforts. However, caution is advised against onerous tax regimes that may impede economic growth. Overall, the research underscores the importance of adopting a balanced and forward-thinking approach to tax policy design, considering the diverse needs and challenges facing economies in the aftermath of the pandemic.